Comparing the diagnostic value of bronchoalveolar lavage fluid galactomannan, serum galactomannanan, and serum 1, 3-β-D-glucan in non-neutropenic respiratory disease patients with invasive pulmonary aspergillosis. Issue 14 (9th April 2021) - Dai, Zhang; Cai, Minjing; Yao, Yihui; Zhu, Jianhui; Lin, Lingqing; Fang, Lili; Li, Zhimeng; Yi, Huochun; Chen, Bo; Liang, Xianming
Abstract : Abstract: The incidence of invasive pulmonary aspergillosis (IPA) is increasing higher in non-neutropenic patients. This study aimed to assess the diagnostic performance of bronchoalveolar lavage fluid (BALF). Galactomannan (GM), serum GM, and 1, 3-β-D-glucan (BDG) in non-neutropenic respiratory disease patients with IPA. A total of 333 non-neutropenic patients suspected IPA were recruited from Xiamen University Zhong Shan hospital between January 2016 and February 2019. One, 33, and 92 cases were diagnosed with proven, and possible IPA. BALF and serum GM were both elevated in the possible IPA group and the probable/proven IPA group ( p  < 0.001). BALF and serum GM showed a fair correlation in the possible IPA group ( r  = 0.286, p  = 0.008), and moderate correlation in the probable/proven IPA group ( r  = 0.466, p  = 0.005). When the cutoff value was 0.5, the sensitivity and negative likelihood ratio of BALF GM were superior to serum GM (78.3% vs 47.8%, 96.7% vs 91.6%). The specificity and positive likelihood ratio of BALF GM were slightly weaker than serum GM (91.8% vs 95.4%, 56.7% vs 85.0%). When the cutoff value was 1.0, the sensitivity and negative predictive value of BALF GM were better than serum GM (73.9% vs 26.1%, 94.5% vs 88.8%), and the specificity of were equivalent (99.2%). The optimal cutoff value of BALF GM was 0.6, wherein the sensitivity reached 78.3% and the specificity reached 95.4%. Given the extremely low sensitivity of serum BDG at different cutoff values (≥10 μg/mL = 5.3%, ≥20 μg/mL = 2.1%), it cannot be used as a preferred biomarker. The diagnostic performance of BALF GM was superior to other biomarkers and the optimal cutoff value was 0.6.